Unveiling the Plight of Child Labour in Nepal’s Hotel and Restaurant Sector (Interdisciplinary Research in Education, 2025)
The aim of this study is to investigate the current situation of child labour in Kathmandu's hotel and restaurant industry. Utilizing a quantitative research design, the study study focuses on male child workers who are employed in hotels, restaurants, tea shops, bus stations, and other informal sectors in Kathmandu. Using the convenient sampling method, a total of 147 male child labourers were selected. Frequency distributions and chi-square tests were used among the univariate, bivariate and multivariate statistical methods. The results showed that the Janajatis and the Dalits were excessively represented among the child labourers, with the majority (61.22%) being between the ages of 12 and 15.  The majority of children were from those families with unstable housing, high parental illiteracy (51.70%), and poor economic circumstances. Of the respondents, more than 81% had dropout of  school, mainly as a result of personal choice, lack of good parenting, or household duties.  These kids were frequently working over 12 hours a day at physically demanding jobs, mainly cooking, dishwashing, and customer service.  Health problems also mainly; skin disease, throat infections, and hand pain were also found with them.  Particularly, 61.2% of the respondents reported that they were unhappy with their jobs.  Working hours and job dissatisfaction (p < 0.01), age and dropout rates (p < 0.05), and parental literacy and school enrolment (p < 0.01) were found statistically significant in the bivariate analysis. These findings denote that child labour has deeper roots in systemic injustice, social marginalisation, and a lack of educational support, not just an economic problem.